Determination of Total Phenolic Compounds and SPF ( Sun Protection Factor)Value of Methanol Extract & Fraction Brotowali Leaves ( Tinospora crispa L.) - Sagala, Zuraida; Panjaitan, Riong Seulina (Indonesian Journal of Pharmaceutical Research, 2023)
Flavonoid is one of the compounds that are important for the body because it has a function as an antidote to free radicals by overcoming and preventing the occurrence of oxidative stress conditions are antioxidants. Phenolic compounds are known to have antioxidant activity due to the substitution of hydroxy groups at the ortho and para positions to the – OH and –OR groups. Phenolic compounds are known to have various pharmacological activities, one of that is photoprotective which useful for protecting the skin from the dangers of UV exposure. Brotowali contains secondary metabolites such as alkaloids, phenolics, steroids, and tannins. The presence of these compounds indicates that brotowali has the ability to inhibit free radical compounds. This study aims to determine the total phenolic levels and SPF (Sun Protection Factor) in methanol extract and leaf fraction of brotowali (Tinospora crispa L.). The research methods include maceration, fractionation, phytochemical screening test, specific and non-specific parameter testing, assay by Folin-Ciocalteau method using gallic acid as a standard, and SPF (Sun Protection Factor) value. Based on the research results obtained, the ethyl acetate fraction of brotowali leaves contains phenolic compounds of 675.6522 mg GAE/gram sample with the highest SPF value at a concentration of 1000ppm of 48.79.